Temporal dynamics of emotional face processing in social anxiety - Ya-Chun Feng; Bo-Cheng Kuo; Wen-Yau Hsu (PLoS ONE, 2025)
Previous studies have demonstrated that emotional facial expressions influence attention and perception in individuals with social anxiety. However, the relative influence of positive versus negative expressions on distinct subprocesses of attention and perception remains unclear. This event-related potential (ERP) study investigates the temporal dynamics of electrophysiological responses to emotional faces in high (HSA; N = 56) or low (LSA; N = 47) social anxiety individuals using a dot-probe task. Four face pairs (angry-neutral, happy-neutral, angry-happy, and neutral-neutral) were presented to probe the influence of positive and negative expressions. While behavioural results showed no significant group differences in attention bias, ERP results showed a reduced N170 amplitude for the HSA vs. LSA group in angry-neutral, happy-neutral, and angry-happy face pairs. Furthermore, enhanced N2pc effects to emotional expressions were found only in the HSA group when angry-neutral and happy-neutral face pairs were presented. No N2pc effect emerged when both positive and negative expressions were presented simultaneously. Finally, no significant P1 effect was found. Together, both positive and negative expressions influenced attentional deployment and face-specific processing in relation to social anxiety. Socially anxious individuals perceived less emotional facial information, yet their attention was biased by both negative and positive expressions.